RFID tracking to study clinical activity in the operating room - Parry, D; Houliston, B; Foy, J (IEEE International Conference on Healthcare Informatics 2014 (ICHI 2014), 2014)
Measuring activity in the operating theatre is a difficult but important task. Using ultra wideband active RFID tags (UWB) we were able to track and Anesthetist and anesthetic technician during a simulated operation. A number of parameters were calculated including gaze direction, distance travelled and separation were calculated. Some characteristic movements were identified, including head and torso rotation. Ultra wideband RFID may form part of a suite of sensors that can begin to identify activity during operations.
Keywords: Anesthesia; Activity analysis; RFID